difference of recursive equations
I think you can just use an induction proof, since you already have an intuition of the result, it is much easier to check :
$$\text{Let : } H_n :"w_n=f(n)-g(n)=4-4n" $$
First, for $n=0$ :
$$w_0=4=4-4\times 0 $$
Hence, $H_0$ is true.
Let $n\in\mathbb{N} $, such that $H_n$ is true, let us show $H_{n+1}$
$$w_{n+1}=3w_n+8n-12=3(4-4n)+8n-12\\
= 12-12n+8n-12=-4n=4-4(n+1) $$
Hence, $H_{n+1} $ is true, so we can conclude that :
$$\forall n \in \mathbb{N}, f(n)-g(n)=4-4n $$
$$d(n+1)=3d(n)+8n-12,\\d(0)=4.$$
The homogeneous solution is
$$d_h(n)=3^nd_h(0).$$
Plugging the initial condition,
$$3^0d_h(0)=3\cdot4+8\cdot0-12=0.$$
Then with the ansatz $d_a(n)=an+b,$
$$an+a+b=3an+3b+8n-12$$ or by identification,$$d_a(n)=4-4n=d(n).$$
There is no need for induction, use a straight proof.
The equation is
$$f(n+1)-g(n+1)=3(f(n)-g(n))+8n-12$$ with $$f(0)-g(0)=4$$ and it does verify the solution
$$f(n)-g(n)=4-4n$$ as is shown by substitution,
$$4-4(n+1)=3(4-4n)+8n-12,$$ equivalent to $$-4n=-4n.$$
Furthermore, $$4=4-4\cdot 0.$$